2010
DOI: 10.1021/cm100224b
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Controlled Synthesis of Iron Silicide (Fe3Si and FeSi2) Nanoparticles in Solution

Abstract: In this study, a high-temperature reduction method is developed to prepare iron silicide nanoparticles in solution phase. The synthesis applies a reaction of silicon tetrachloride with iron pentacarbonyl in the presence of 1,2-hexadecanediol to form iron silicide nanoparticles. Under iron-rich synthetic conditions, superparamagnetic Fe3Si nanoparticles form. The saturation magnetization of Fe3Si nanoparticles has been found to be 60 emu/g by superconducting quantum interference device (SQUID) magnetometry tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 37 publications
2
59
0
Order By: Relevance
“…In their bulk state, Fe 3 Si and Fe 3 C possess a relatively high saturation magnetization value of 84 emu g -1 and 130 emu g -1 . 202, 203 These materials are known to be more resistant to oxidation than iron nanoparticles. They can therefore maintain their original magnetic properties for long-term biomedical applications.…”
Section: Synthesis Of Core Magnetic Nanoparticlesmentioning
confidence: 99%
“…In their bulk state, Fe 3 Si and Fe 3 C possess a relatively high saturation magnetization value of 84 emu g -1 and 130 emu g -1 . 202, 203 These materials are known to be more resistant to oxidation than iron nanoparticles. They can therefore maintain their original magnetic properties for long-term biomedical applications.…”
Section: Synthesis Of Core Magnetic Nanoparticlesmentioning
confidence: 99%
“…However, only very few chemical synthesis techniques are available in the literature. Dahal et al [20] has reported synthesis technique for iron silicide using chemical reaction between iron pentacarbonyl (Fe(CO) 5 ) and silicon tetrachloride (SiCl 4 ). On the other hand, Bywalez et al [21] realized gas phase synthesis of ␤-FeSi 2 nano-particles by controlled thermal decomposition of iron pentacarbonyl and monosilane at about 900 • C. Although these synthesis techniques are quite novel and contemporary, their significant draw backs are the generation of by-product phases such as -FeSi, Fe 3 Si, ␣-FeSi 2 and Fe 5 Si 3 [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Dahal et al [20] has reported synthesis technique for iron silicide using chemical reaction between iron pentacarbonyl (Fe(CO) 5 ) and silicon tetrachloride (SiCl 4 ). On the other hand, Bywalez et al [21] realized gas phase synthesis of ␤-FeSi 2 nano-particles by controlled thermal decomposition of iron pentacarbonyl and monosilane at about 900 • C. Although these synthesis techniques are quite novel and contemporary, their significant draw backs are the generation of by-product phases such as -FeSi, Fe 3 Si, ␣-FeSi 2 and Fe 5 Si 3 [20,21]. The gas phase synthesis technique developed by Bywalez et al requires high temperature in the synthesis of ␤-FeSi 2 [21] as well as restricted, expensive and toxic chemicals like iron pentacarbonyl, silane gas are used for the synthesis of iron di-silicide [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The silicides are the materials that the solution-based synthetic process for nanoparticles, which is widely applied to noble metals and metal oxides, is difficult to apply. Recently, it was reported [5] that Fe 3 Si nanoparticles is prepared by a high temperature reduction method in solution phase. However, the phase control synthesis and the fabrication of composite particulates would still be challenging for silicides.…”
Section: Introductionmentioning
confidence: 99%